A distribuição funcional do fitoplâncton prediz a variabilidade ambiental entre dois rios subtropicais - Aquino, Camila Akemy Nabeshima (2017)
Phytoplankton traits diversity provides a powerful means to addressing ecology’s questions, and can be 43 adopted to simplify and predict the community structure, in function of the multiples environmental filters 44 that operate in the different ecosystems. Thus, we evaluated the response of phytoplankton functional 45 groups of two subtropical rivers in a temporal scale, identifying the main environmental filters associated 46 with the presence of the different groups and their functional traits during a seasonal cycle. Using 47 multivariate analysis, we found an environmental dissimilarity predicted by the presence of different 48 functional groups in the rivers. Six GFs were recorded: J (chlorophyceans chlorococcales), M (colonial 49 cyanobacteria), N (desmids), W1 (euglenophyceans), X2 (flagellated unicellular chlorophyceans) and F 50 (flagellated colonial chlorophyceans). The GFs J, M and N were exclusive to the first river, while X2 and 51 F were exclusive to the second river. GF W1 was recorded in both rivers, however, its greatest 52 contribution occurred to the second river. Thus, the GFs reflected the environmental dissimilarity, mainly 53 related to the conditions of water flux, conductivity, light availability and depth of the environments. In 54 view of the obtained results, the functional grouping considered a relevant tool in phytoplankton ecology, 55 offers a practical means to investigating the relation between phytoplankton and ecosystem functioning, 56 and consequently can assist in decision-making for the management and conservation of the biodiversity 57 in lotic environments